2011
DOI: 10.4000/cea.204
|View full text |Cite
|
Sign up to set email alerts
|

Trauma e Limpeza Ritual de Veteranos em Moçambique

Abstract: trauma e limpeza ritual de veteranos em moçambique Resumo O presente artigo descreve e discute os rituais de limpeza oficiados aos veteranos da guerra civil de Moçambique por parte de médicos tradicionais do sul do país. Reinventados nas últimas décadas, a partir de tratamentos para outras situações e importando a sua lógica explicativa, esses rituais apresentam uma eficácia na reintegração social dos veteranos que se deve em grande medida à coerência que mantêm com os sistemas locais de interpretação do infor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 3 publications
0
3
0
2
Order By: Relevance
“…These were rituals that enhanced the healing of trauma and restored the balance between humans and spirits and were used to incorporate combatants and war-affected civilians into their families and communities (Cobban 2007;Granjo 2007aGranjo , 2007bGraybill 2004;Honwana 2005Honwana , 2006Lundin 1998;Nordstrom 1997: 145-146). In an evaluation of the process of reintegration of demobilizados in Mozambique, Alden (2002: 353) suggested that traditional mechanisms substantially aided in the 'fading away' of ' old soldiers' (see also Boothby 2006).…”
Section: War Andmentioning
confidence: 99%
“…These were rituals that enhanced the healing of trauma and restored the balance between humans and spirits and were used to incorporate combatants and war-affected civilians into their families and communities (Cobban 2007;Granjo 2007aGranjo , 2007bGraybill 2004;Honwana 2005Honwana , 2006Lundin 1998;Nordstrom 1997: 145-146). In an evaluation of the process of reintegration of demobilizados in Mozambique, Alden (2002: 353) suggested that traditional mechanisms substantially aided in the 'fading away' of ' old soldiers' (see also Boothby 2006).…”
Section: War Andmentioning
confidence: 99%
“…Além do impacto dos espíritos nas guerras históricas (Honwana, 2003, p. 71-74;Langa, 1992, p. 29-32, p. 43-46), hoje em dia, na mais recente era pós-guerra depois de uma guerra civil de dezesseis anos (cerca de 1976 a 1992), existem preocupações sobre uma nova onda de espíritos em busca de vingança (Mahumana, 2013, p. 117-8, p. 176;Fry, 2000, p. 80;Igreja et al, 2008). Agora que os soldados que foram submetidos a rituais de limpeza (Granjo, 2011) estão ficando velhos e morrendo, os espíritos que foram temporariamente acalmados pelos rituais voltarão a se tornar ativos, porque ainda estão em busca de vingança. De acordo com ambos os curandeiros e pastores pentecostais, existem espíritos vingativos ativos em cada família alargada.…”
Section: Marido Espiritualunclassified
“…Paradoxically, by actualizing that which should not be realized, the former serves as a vehicle for the coming into being of the latter. In Paulo Granjo's lucid account of divination practices in southern Mozambique (; see also Granjo ; Honwana ), he thus describes how alternative futures might be accessed by manipulating the probabilities for the likely, albeit unwanted, (future) outcomes of current actions. Through divinatory practices, the productive potentials of the future are elicited by actively altering the conditions (in the present) for what lies ahead.…”
Section: Presents Without Futuresmentioning
confidence: 99%